Internship at la Ribera School: Bilingualism for peace program (2023)
This paper aims to present my internship experience in the Bilingualism for Peace Program, which was carried out through face-to-face classes at La Ribera High School in Monteria, Córdoba. I dedicated complete teaching English to 3 groups such as: Elementary, Intermediate, and Conversation level with students belonging to, 5, 6,7, 8, 9, 10 and 11 grades. One of the major challenges encountered during this internship was the difficulty among students to achieve one of the program's objectives, which aimed to promote a peaceful environment and global social competences through the target language. It was clear that strong pedagogical strategies were needed to address these barriers, encourage active student participation, and promote oral interaction within the classroom, as well as intercultural awareness. This is why I considered the importance of integrating cultural elements, using innovative methods, and providing resources that stimulate their interest and motivation. Nevertheless, my principal purpose was focused on the implementation of role play as a didactic strategy through platforms such as TikTok to promote active learning where students found it easier to learn difficult concepts by simulating a scenario where they had to apply these concepts, all this through lesson plans based on Task-Based Language Teaching. Each of these classes had the main objective of encouraging more motivation by the student's part to question themselves but above all to respectfully address controversial issues, such as Racism, Diversity, Culture, Gender, Bullying, Inclusion, Diversity, and not least the fact of how to be a good human being in our society. All this accompanied by essential factors of the program such as Interculturality and all the values that go hand in hand with peace.